The Effect of a 4-Week TRX Suspension Training on Lower Extremity Alignment and Muscle Strength in Male Basketball Players - Mohammad seyedahmadi; Karim Khalaghi; Ahmad Aghaei; Maliheh Ardakanizade (Journal of Rehabilitation Sciences and Research, 2025)
Background: This study investigated the effectiveness of a 4-week TRX suspension training program on knee and hip alignment as well as hip muscle strength in male basketball players with dynamic knee valgus. Methods: The present study was Quasi-experimental, and its statistical population consisted of basketball players (18-25 years old) from Mashhad, Iran. Thirty-two athletes diagnosed with dynamic knee valgus were randomly selected as samples and randomly assigned to experimental (n=16) and control (n=16) groups. Data measurement tools included Kinovea software (Kinovea Robotics, Canada, 2006) and an isokinetic dynamometer (JTECH MedicalTM Commander instruments). To measure kinematic angles, athletes performed standardized tasks such as squats and lunges, which were selected to elicit dynamic knee valgus and accurately assess knee and hip alignment.  A 4-week TRX suspension training program (3 sessions/week, 30-45 minutes/session) was implemented for the exercise group. Statistical analyses (paired t-tests, ANCOVA) were conducted using SPSS software (p < 0.05). Results: Paired-sample t-tests revealed significant improvements in knee and hip alignment (reduced knee valgus (p=0.003) and hip drop angles (p=0.013)) in the exercise group post-training compared to pre-training. The exercise group's dominant leg also observed significant increases in hip abductor, extensor, and external rotator strength (p=0.0001). Analysis of covariance (ANCOVA) controlling for pre-test scores demonstrated significant between-group differences in all outcome measures, indicating the TRX program's effectiveness in the dynamic knee valgus group compared to the control. Conclusion: This study suggests that a 4-week TRX suspension training program can effectively improve knee and hip alignment and strengthen hip musculature in male basketball players with dynamic knee valgus.